2021
DOI: 10.1016/j.ssresearch.2020.102459
|View full text |Cite
|
Sign up to set email alerts
|

Demographic change and the 2016 presidential election

Abstract: The election of Donald Trump raised many questions about the impact of immigration on American politics. This article asks whether backlash to demographic change in counties undergoing rapid growth in foreign-born, Hispanic, and/or Asian populations may have played a role in his election. I use techniques accounting for selection into treatment to examine the relationship between demographic changes at the county level and voting patterns in the 2016 presidential election. Analyzing individual-level survey dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Observational research suggests that outgroup growth is a more reliable correlate of attitudes than outgroup size (e.g., Hopkins 2010; Maggio 2020; Newman 2013). 3 In fact, a substantial body of research suggests that stable interpersonal contact can actually reduce intergroup hostility and prejudice (Pettigrew and Tropp, 2006).…”
Section: Responses To the Growing Latino Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational research suggests that outgroup growth is a more reliable correlate of attitudes than outgroup size (e.g., Hopkins 2010; Maggio 2020; Newman 2013). 3 In fact, a substantial body of research suggests that stable interpersonal contact can actually reduce intergroup hostility and prejudice (Pettigrew and Tropp, 2006).…”
Section: Responses To the Growing Latino Populationmentioning
confidence: 99%
“… 9 See Maggio (2020) for a discussion of the advantages and disadvantages of operationalizing growth as percentage point change or percentage change. …”
Section: Notesmentioning
confidence: 99%
“…The evidence indicates that the rapid demographic shifts caused by mass‐migration have cumulatively undermined social cohesion, trust, and collective solidarity among lower middle and working classes communities in Western democracies (Alesina & La Ferrara, 2002; Kaufmann & Goodwin, 2018; Maggio, 2021; Putnam, 2007). 3 Given that communal ties and local attachments appear to be disintegrating, it is of little surprise that liberal nationalism has been proposed as a via media between neoliberal globalism and the reactionary instances of populism which are excessively chauvinistic and xenophobic.…”
Section: Liberal Nationalism and The Ascent Of National Populismmentioning
confidence: 99%
“…In terms of demographic change at the local level (rather than the country level), while residential selection or adaptation to the local environment over the long-term may lead to more positive attitudes for those living near immigrant-origin groups, the sudden disruption of the demographic status quo may generate resentment and subsequent Backlash (Hopkins 2009). This can take various forms, such as conservative turns in policy and voting (Becker and Fetzer 2017; Enos 2017; Hopkins 2009, 2010; Maggio 2021; Marquez and Schraufnagel 2013; Newman et al 2012; Pedroza 2019; but see Arzheimer and J. M. Carter 2006; Chavez and Provine 2009), and even hate crimes 6 (Grattet 2009; Green, Strolovitch, and Wong 1998; Lyons 2008; Stacey, Carbone-López, and Rosenfeld 2011). In terms of immigration attitudes and related outcomes, such as attitudes toward immigrant-origin ethnic minorities, various studies have linked these outcomes to local demographic change (Gijsberts and Dagevos 2007; Kawalerowicz 2021; Newman and Johnson 2012), though not in all circumstances (Hjerm 2009; Walker 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the mid-1990s, however, White immigration attitudes in the United States have undergone a massive liberalization. Focusing on White likely voters, Michael Hout and Christopher Maggio (2021) show that, from 1994 to 2018, support for reducing the number of immigrants decreased by around 25 percentage points. Other studies have found a similar liberalization in immigration attitudes in recent decades (Gallup 2020; Jones 2019; Saad 2013), with the notable feature of partisan polarization highlighting a divide between liberal Democrats and restrictive Republicans.…”
Section: Introductionmentioning
confidence: 99%